Oxidação por plasma eletrolítico em superfícies de alumínio comercial - Tavares, Matheus de Medeiros (Universidade Federal Rural do Semi-Árido, 2018)
Aiming at increasing hardness and wear resistance on pure commercial aluminum surfaces, aluminum oxide coatings were produced by Electrolytic Plasma Oxidation (PEO). For this, a pulsed current was used, where treatments with 30% and 50% duty cycles were performed, varying the current density (9, 12 and 15 A/dm2) and the treatment time ( 2, 6 and 12 minutes) in each cycle. Voltage-time studies were carried out to characterize the process micro-discharges. In addition, X-ray diffraction (XRD), scanning electron microscopy (SEM), nanohardness, scratching test and calotest were performed to characterize the coatings. The results indicated that the treatment was efficient to produce a uniform and consistent coating of aluminum oxide with γ-Al2O3 as the major phase. It has been observed that porosity and average pore size tend to increase when the duty cycle and current density increase. In addition, the thicker coatings were observed in the treated samples for longer periods. Increases in surface nanohardness were observed in all samples treated by PEO, regardless of the treatment parameters. Surfaces coated with aluminum oxide showed high resistance to scratching, especially thicker surfaces. The treatment was effective in improving the wear resistance by up to 48%. It was concluded that the best mechanical and tribological properties are directly related to the morphologies of the less porous surfaces, with smaller pore size and greater layer thickness of oxide
Keywords: Alumínio; Óxido de alumínio; Revestimento; PEO; Desgaste; Aluminum; Aluminum oxide; Coating; PEO; Wear; ENGENHARIAS::ENGENHARIA DE MATERIAIS E METALURGICA